Perceived usefulness and effectiveness of a MOOC on healthcare during the pandemic - José Miguel Padilha; Celeste Bastos; Francisco Vieira; Paulo Machado; Ana Leonor Ribeiro; Pedro Cabral; Margarida Abreu (Humanities & Social Sciences Communications)
Abstract The COVID-19 pandemic has posed significant constraints to healthcare professionals in accessing evidence-based and certified education. This has highlighted the need for massive open online courses (MOOCs), considering their flexibility in digital access and time management. This study aimed to assess the intention of healthcare professionals to use a MOOC in lifelong learning during a pandemic outbreak and its effectiveness in knowledge retention. A descriptive study was conducted involving 2629 participants enrolled in a COVID-19-related open-access MOOC who agreed to participate in this study. A validated questionnaire was applied to collect the data. Data were processed and analysed using descriptive and inferential statistics. The study revealed the existence of certified trainees and non-certified explorers. The MOOC was useful to the healthcare professionals’ lifelong training (mean of 4.4 in 5) and perceived ease of use (mean of 4.4 in 5), with most professionals intending to continue using lifelong training (mean of 4.4 in 5). Moreover, participants reported high levels of satisfaction (4.5 in 5). The analysis of the mean score of the initial and final assessment per participant showed statistically significant differences (t 795 = 58.5; P < 0.001; d = 0.19), confirming the programme’s effectiveness in knowledge retention. Findings also reveal higher completion rates (32.2%) compared to the literature (~12%), emphasising the importance of implementing a learning experience tailored to reskilling based on practical, collaborative, and dynamic content. These study results underscore the perceived ease of use, usefulness, and the intention of healthcare professionals to use MOOCs in lifelong learning and demonstrate their effectiveness in knowledge retention. Results emphasise the need for developing modular, practical, interactive, collaborative and immersive learning experiences to increase completion rates and meet the needs of professionals in this area.